Assessing the interrelatedness of multiple types of adverse childhood experiences and odds for poor health in South Carolina adults. (March 2017) - Crouch, Elizabeth; Strompolis, Melissa; Bennett, Kevin J.; Morse, Melanie; Radcliff, Elizabeth
Abstract: Adverse childhood experiences (ACEs) have been linked to negative health outcomes in adulthood, but little research has been done on the effect of ACEs on the health and well-being of adults in South Carolina (SC). This study analyzed a sample of 9744 respondents who participated in the 2014 South Carolina Behavioral Risk Factor Surveillance System (BRFSS) to examine the relationship among childhood experiences of physical, sexual, and emotional abuse, as well as witnessing household violence, on mental and physical health outcomes in adulthood among SC residents. Twenty-two percent of survey respondents reported poor general health (22.1%), and a smaller proportion reported high frequent mental distress in the past month (13.1%). Each category of childhood experiences was associated with an increase in the risk of poor general health. Individuals reporting three or more types of experiences were more likely to report poor health (aOR 2.89; 95% CI 2.86–2.92) than adults without such experiences. Respondents reporting three or more types of childhood adverse experiences were more likely to report frequent mental distress (aOR 3.29; 95% CI 3.26–3.33) compared to adults who did not report three or more types of adversity. Findings from the SC BRFSS highlight a connection between ACEs and negative health outcomes later in life. Given that results of this study also demonstrated that increased exposure to ACEs was associated with greater odds of negative health in adulthood, preventing adverse events such as experiencing abuse or witnessing domestic violence in childhood will have significant effects on later adult health.